Dickkopf 3—a novel biomarker of the 'kidney injury continuum'. Issue 5 (5th February 2020) - Schunk, Stefan J; Speer, Thimoteus; Petrakis, Ioannis; Fliser, Danilo
Abstract: Chronic kidney disease (CKD) is a global public health problem accompanied by substantial comorbidities and reduced life expectancy. In this respect, progressive CKD leading to uraemia can be seen as a systemic disease with a critical impact on virtually all organ systems. Therefore, it is of particular importance to identify patients with ongoing CKD progression, which is challenging, because the individual course of CKD is difficult to predict. Patterns of progression in CKD patients include linear and non-linear trajectories of GFR loss, but kidney function can also remain stable for years. Moreover, a substantial GFR decline may occur in the absence of higher-grade albuminuria (non-proteinuric CKD), rendering the measurement of albuminuria less reliable for progression prediction in such individuals. In the present review, we focus on the recently identified glycoprotein Dickkopf-3 (DKK3) as a stress-induced, renal tubular epithelial cell-derived, pro-fibrotic molecule. In experimental CKD models, DKK3 promoted renal tubulointerstitial fibrosis through modulation of the canonical Wnt/β-catenin signalling pathway. In clinical studies, increased urinary DKK3 levels identified patients at high risk for short-term CKD progression, regardless of the cause of kidney disease, baseline kidney function and albuminuria. Moreover, increased urinary DKK3 levels are associated with a high risk for acute kidney injury and the subsequent loss of kidney function after cardiac surgery. These findings highlight DKK3 as a mediator of renal tubular cell damage in kidney injury and short-term progression of kidney disease, with potential therapeutic implications.